ANALISIS PENGARUH TOTAL SERVICE QUALITY MANAGEMENT TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI - Ika Nurul Qomari; Afrizal Rahman (Universitas Muhammadiyah Semarang, 2011)
AbstractThis research was conducted to analyze the influence of Total Service Quality Management to the customers satisfaction (the customers in this research were the user servicing Persada Tour & Travel of Yogyakarta agency) by using 5 dimensions of TSQM: physical quality dimension, supporting physical Quality, company/institution quality, technical Quality dimension, and interactive quality dimension.The method used for data collecting was survey method by giving question naires to the respondents. The technique used to take the samples of the research was purposive sampling. In this research validity and Reliability tests were conducted to ensure the validity and reliability of the research instruments. Data Analyzed used in the research were multiple linear regression, t test, and F test.The result of the research shows that there is an influence of Total Service Quality Management to the customers satisfaction on the dimensions of physical quality, supporting physical quality